Reduction of angular members of boundary integral equations of thin plate bending - Бродовий, В. Л. (Proceedings of National Aviation University (archive), 1998)
The problem of angular points and angular non-integral members in numerical solution of plate bending integral equations is under consideration. A transformation of the members based upon the condition of full moment continuity in an angular point is proposed which allows reducing the additional members to corrections added to main coefficients. Formulae are obtained for linear non- consistent approximation of potentials densities